Media Pembelajaran Anak Berkebutuhan Khusus (ABK) - Sya'dullah, Ahmad (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2020)
Abstract : Children with special needs (ABK) are children who have special characteristics and different from children as usual, in other words they are not able to shows mental, emotional or physical disabilities, which are included in the category of ABK between others: visually impaired, deaf, mentally retarded, physically disabled, mentally retarded, learning difficulties, and behave. Barriers to the education of children with special needs require the form of educational services according to their abilities and potential. Process learning requires special training for teachers who want a career in education for ABK. Interaction between ABK students and teachers requires a way of communication continuously in which there is a process of motivating each other. The method used in this study is a qualitative research method with observe phenomena such as behavior, perceptions, motivations, actions, and others holistically and descriptive. The validity of the data in this study uses a source triangulation technique or data triangulation. Source triangulation here is not only on one source, but more than one source one source, through interviews, researchers can obtain information clearly and structured. The results of the research conducted by the author is the difficulty of interaction between teachers, normal students and ABK students, because ABK students not only communicate by verbal, but there are also those who have to use non-verbal communication. Barriers and support teachers in interacting with special needs students, the obstacle is often a misunderstanding between ABK students with teachers and their support is the teacher makes inclusive classes as support education for ABK students. The dynamics of the personal interaction of teachers and students with special needs, the occurrence of the difficulty of delivering teachers to students, due to the unification of normal students and students ABK students in regular classes. ABK students have low communication skills and cause communication tends to run in one direction.